Formation and Dissociation of Methane Hydrates from Seawater in Consolidated Sand: Mimicking Methane Hydrate Dynamics beneath the Seafloor - Prasad Kerkar; Kristine Horvat; Devinder Mahajan; Keith Jones (Energies, 2013)
Methane hydrate formation and dissociation kinetics were investigated in seawater-saturated consolidated Ottawa sand-pack under sub-seafloor conditions to study the influence of effective pressure on formation and dissociation kinetics. To simulate a sub-seafloor environment, the pore-pressure was varied relative to confining pressure in successive experiments. Hydrate formation was achieved by methane charging followed by sediment cooling. The formation of hydrates was delayed with increasing degree of consolidation. Hydrate dissociation by step-wise depressurization was instantaneous, emanating preferentially from the interior of the sand-pack. Pressure drops during dissociation and in situ temperature controlled the degree of endothermic cooling within sediments. In a closed system, the post-depressurization dissociation was succeeded by thermally induced dissociation and pressure-temperature conditions followed theoretical methane-seawater equilibrium conditions and exhibited excess pore pressure governed by the pore diameter. These post-depressurization equilibrium values for the methane hydrates in seawater saturated consolidated sand-pack were used to estimate the enthalpy of dissociation of 55.83 ± 1.41 kJ/mol. These values were found to be lower than those reported in earlier literature for bulk hydrates from seawater (58.84 kJ/mol) and pure water (62.61 kJ/mol) due to excess pore pressure generated within confined sediment system under investigation. However, these observations could be significant in the case of hydrate dissociation in a subseafloor environment where dissociation due to depressurization could result in an instantaneous methane release followed by slow thermally induced dissociation. The excess pore pressure generated during hydrate dissociation could be higher within fine-grained sediments with faults and barriers present in subseafloor settings which could cause shifting in geological layers.